Experiences of Children With Gay Fathers. (December 2016) - Perrin, Ellen C.; Pinderhughes, Ellen E.; Mattern, Kathryn; Hurley, Sean M.; Newman, Rachel A.
An online survey was distributed via snowball sampling and resulted in responses from 61 gay fathers raising children in 2 states. Fathers reported on the barriers they experienced and the pathways they took to becoming parents. They reported also on experiences of stigma directed at them and their children, especially from family members, friends, and people in religious institutions. Despite these difficulties they reported that they engaged actively in parenting activities and that their child(ren)'s well-being was consistent with national samples.